Individual and combined effects of land use/cover and climate change on Wolf Bay watershed streamflow in southern Alabama. Issue 22 (24th September 2013) - Wang, Ruoyu; Kalin, Latif; Kuang, Wenhui; Tian, Hanqin
Abstract Land use/cover (LULC) and climate change are two main factors affecting watershed hydrology. In this paper, individual and combined impacts of LULC and climate change on hydrologic processes were analysed applying the model Soil and Water Assessment Tool in a coastal Alabama watershed in USA. Temporally and spatially downscaled Global Circulation Model outputs predict a slight increase in precipitation in the study area, which is also projected to experience substantial urban growth in the future. Changes in flow frequency and volume in the 2030s (2016–2040) compared to a baseline period (1984–2008) at daily, monthly and annual time scales were explored. A redistribution of daily streamflow is projected when either climate or LULC change was considered. High flows are predicted to increase, while low flows are expected to decrease. Combined change effect results in a more noticeable and uneven distribution of daily streamflow. Monthly average streamflow and surface runoff are projected to increase in spring and winter, but especially in fall. LULC change does not have a significant effect on monthly average streamflow, but the change affects partitioning of streamflow, causing higher surface runoff and lower baseflow. The combined effect leads to a dramatic increase in monthly average streamflow with a stronger increasing trend in surface runoff and decreasing trend in baseflow. Copyright © 2013 John Wiley & Sons, Ltd.